MO077TEN YEAR TRENDS IN PAEDIATRIC RENAL REPLACEMENT THERAPY IN EUROPE: DATA FROM THE ESPN/ERA-EDTA REGISTRY. (6th June 2020) - Bonthuis, Marjolein; Harambat, Jerome; Vidal, Enrico; Jager, Kitty J
Abstract: Background and Aims: The ESPN/ERA-EDTA Registry includes data on children with end-stage kidney disease receiving renal replacement therapy (RRT) in Europe for 10 consecutive years. We examined time trends in incidence, prevalence and patient survival for paediatric RRT in Europe. Method: We included all children aged < 15 years starting RRT in 22 European countries from 2007 to 2016. General population statistics were derived from Eurostat. Incidence and prevalence were expressed per million age related population (pmarp) and time trends were studied with Joinpoint regression. We analyzed patient survival using Cox regression. Results: The incidence of children commencing RRT < 15 years remained stable over the past ten years, varying between 5.5 pmarp to 6.5 pmarp. The incidence by treatment modality did not change over time: 2.0 to 3.0 pmarp for haemodialysis (HD) and peritoneal dialysis (PD) and 1.0 pmarp for transplantation. Overall prevalence rose by 2% annually (95% CI: 1.5-2.3%) from 29.5 pmarp in 2007 to 35.6 pmarp in 2016. The increase in prevalence was observed in all age categories, but was strongest among children older than 5 years at RRT initiation. The prevalence of patients on all treatment modalities increased during the study period: from 4.5 to 5.4 pmarp for HD, from 4.9 pmarp to 6.0 pmarp for PD and from 19.6 to 23.9 pmarp for transplantation (Figure). Four-year adjusted patient survival on RRT was around 96% and similar for those initiating from 2007-2009 and from 2010-2012 (adjusted HR: 0.97, 95% CI: 0.69-1.36). Conclusion: Over the past decade we found a stable incidence and an increasing prevalence of European children on RRT. Four-year patient survival was good, and did not change over time. These data are important to inform patients and healthcare providers and to aid health policy makers on future resource planning of pediatric RRT in Europe.